Characterization of a human preadipocyte cell strain with high capacity for adipose differentiation - Wabitsch, M; Brenner, RE; Melzner, I; Braun, M; Möller, P; Heinze, E; Debatin, K-M; Hauner, H (International Journal of Obesity, 2001)
To develop and to characterize a human preadipocyte cell strain with high capacity for adipose differentiation serving as a model for studying human adipocyte development and metabolism in vitro. Cells were derived from the stromal cells fraction of subcutaneous adipose tissue of an infant with Simpson-Golabi-Behmel syndrome (SGBS). Adipose differentiation was induced under serum-free culture conditions by exposure to 10 nM insulin, 200 pM triiodothyronine, 1 microM cortisol and 2 microM BRL 49653, a PPAR gamma agonist. During the differentiation process SGBS cells developed a gene expression pattern similar to that found in differentiating human preadipocytes with a characteristic increase in fat cell-specific mRNAs encoding lipoprotein lipase (LPL), glycero-3-phosphate dehydrogenase (GPDH), GLUT4, leptin and others. Differentiated SGBS cells exhibited an increase in glucose uptake upon insulin stimulation and in glycerol release upon catecholamine exposure. SGBS adipocytes were morphologically, biochemically and functionally identical to in vitro differentiated adipocytes from healthy subjects. However, while preadipocytes from healthy control infants rapidly lost their capacity to differentiate after a few cell divisions in culture, SGBS cells maintained their differentiation capacity over many generations: upon appropriate stimulation 95% of SGBS cells of generation 30 developed into adipocytes. A mutation in the glypican 3 gene was not detected in the patient. Thus, it remains unclear whether the molecular alteration in SGBS cells is also responsible for the high differentiation capacity and further investigations are required. The human cell strain described here provides an almost unlimited source of human preadipocytes with high capacity for adipose differentiation and may, therefore, represent a unique tool for studying human fat cell development and metabolism. International Journal of Obesity (2001) 25, 8-15